Fabrication and properties of a high-performance chlorine doped graphene quantum dot based photovoltaic detector1. Issue 37 (25th April 2015) - Zhao, Jianhong; Tang, Libin; Xiang, Jinzhong; Ji, Rongbin; Hu, Yanbo; Yuan, Jun; Zhao, Jun; Tai, Yunjian; Cai, Yuhua
<x xml:space="preserve">Abstract</x> The presence of chlorine doped graphene quantum dots (Cl-GQDs) in the active material can significantly enhance the performance of organic photovoltaic devices.